Pengaruh kepemimpinan dan komunikasi terhadap kinerja karyawan pada Bank BTPN KCP Blitar - Diana Nata Sari; Bambang Septiawan (Insight Management Journal, 2021)
This study aims to: determine whether leadership affects the performance of employees of Bank BTPN KCP Blitar, find out whether communication affects the performance of employees of Bank BTPN KCP Blitar, find out whether leadership and communication together affect the performance of employees of Bank BTPN KCP Blitar. The object of this research is all employees of Bank BTPN KCP Blitar. The data in this study were taken from the results of questionnaires, observations, and documentation. The type of data used in this study is quantitative data type with data sources namely primary data and secondary data. The results showed that the leadership variable partially had a significant effect on the employee performance variable. The communication variable partially has no significant effect on the employee performance variable. Leadership and communication variables simultaneously have a significant effect on employee performance variables